Simultaneous biodegradation of three mononitrophenol isomers by a tailor‐made microbial consortium immobilized in sequential batch reactors. (30th January 2017) - Fu, H.; Zhang, J.‐J.; Xu, Y.; Chao, H.‐J.; Zhou, N.‐Y.
Abstract: The ortho ‐nitrophenol (ONP)‐utilizing Alcaligenes sp. strain NyZ215, meta ‐nitrophenol (MNP)‐utilizing Cupriavidus necator JMP134 and para ‐nitrophenol (PNP)‐utilizing Pseudomonas sp. strain WBC‐3 were assembled as a consortium to degrade three nitrophenol isomers in sequential batch reactors. Pilot test was conducted in flasks to demonstrate that a mixture of three mononitrophenols at 0·5 mol l −1 each could be mineralized by this microbial consortium within 84 h. Interestingly, neither ONP nor MNP was degraded until PNP was almost consumed by strain WBC‐3. By immobilizing this consortium into polyurethane cubes, all three mononitrophenols were continuously degraded in lab‐scale sequential reactors for six batch cycles over 18 days. Total concentrations of ONP, MMP and PNP that were degraded were 2·8, 1·5 and 2·3 mol l −1 during this time course respectively. Quantitative real‐time PCR analysis showed that each member in the microbial consortium was relatively stable during the entire degradation process. This study provides a novel approach to treat polluted water, particularly with a mixture of co‐existing isomers. Significance and Impact of the Study: Nitroaromatic compounds are readily spread in the environment and pose great potential toxicity concerns. Here, we report the simultaneous degradation of three isomers of mononitrophenol in a single system by employing a consortium of three bacteria, both in flasks and lab‐scale sequential batch reactors. The results demonstrate that simultaneous biodegradation of three mononitrophenol isomers can be achieved by a tailor‐made microbial consortium immobilized in sequential batch reactors, providing a pilot study for a novel approach for the bioremediation of mixed pollutants, especially isomers present in wastewater. Abstract : Significance and Impact of the Study: Nitroaromatic compounds are readily spread in the environment and pose great potential toxicity concerns. Here, we report the simultaneous degradation of three isomers of mononitrophenol in a single system by employing a consortium of three bacteria, both in flasks and lab‐scale sequential batch reactors. The results demonstrate that simultaneous biodegradation of three mononitrophenol isomers can be achieved by a tailor‐made microbial consortium immobilized in sequential batch reactors, providing a pilot study for a novel approach for the bioremediation of mixed pollutants, especially isomers present in wastewater.